"We make new families:" findings from a family court mediation study. (15th June 2022) - Crampton, Alexandra
Abstract: Mediation was brought into family court cases as a divorce litigation alternative. Today, parents are not only encouraged but mandated across most U.S. states to consider mediation before further court action can be taken. Research has not kept up with understanding how publicly mandated and subsidized mediation services become part of court cases and possible case resolution. This article reviews how mediation has evolved from outside alternative to family court "workhorse" within a family dispute resolution paradigm centered on shared parenting as in the best interest of children. Research results from a family court mediation program are presented to highlight how parents encountered and responded to mediation as an embedded part of today's family dispute resolution paradigm/court system. Especially in cases that keep coming back to court, family dispute resolution has become a means of "making family" as much as supporting family separation. Implications for practice include limitations of a mediation service as provided in an under‐resourced court and ultimate reliance upon parents to uphold the best interest standard through ongoing co‐parenting interactions. Key points for the family court community: Mediation was brought into family law to as a divorce litigation alternative in the wake of "no‐fault" family law reforms in the 1970s and 1980s. The evidence base for mandated mediation in child custody cases continues to lie primarily from studies of divorce cases and of mediation as divorce litigation alternative. However, divorce is only one reason why today's litigants file child custody cases. This study provides empirical data on how today's parents engage in mandated mediation services through focus in one U.S. family court program. This article calls for an updated research paradigm in which mandated mediation provides more than a litigation alternative and, in some cases, becomes a means through which the state is "making family" through pressuring parents to share parenting responsibilities.